Effect of GR24 on the growth and development of licorice under low phosphorus stress - Yuting Jing; Man Li; Yong Wu; Chengming Zhang; Chengshu Qiu; Hengming Zhao; Li Zhuang; Hongling Liu (PeerJ)
Background Glycyrrhiza, a perennial herbaceous medicinal plant, is extensively utilized in the pharmaceutical industry. The growth of Glycyrrhiza is frequently constrained by soil phosphorus availability, as a significant portion of arable land in China suffers from phosphorus deficiency. Method This study utilized Ural Glycyrrhiza uralensis Fisch as the subject and examined the application of GR24, a synthetic strigolactone, under three phosphorus conditions: none (P1), low (P2), and high (P3). The research aimed to ascertain the optimal concentration of GR24 for promoting licorice growth and development, thereby providing a theoretical foundation for its agricultural management. Results The optimal GR24 concentration for P3 and P2 conditions was identified as G3 (10 µM), which enhanced growth metrics, chlorophyll a and b levels, while also boosting antioxidant enzyme activities in licorice. Specifically under P3, significant increases in liquiritigenin and glycyrrhizic acid levels were observed. Under P2, increases were noted in isoliquiritigenin, liquiritigenin, and liquiritin levels. Transcriptome analysis revealed differential gene, with 137 and 270 genes up-regulated and 77 and 294 genes down-regulated in the P3 and P2 treatments, respectively. GO functional enrichment identified 132 and 436 differentially expressed genes for P3 and P2 respectively, while KEGG pathways were predominantly enriched in plant-pathogen interactions and phenylpropanoid biosynthesis. Application of GR24 in P1 conditions did not significantly affect growth indices but did enhance glycyrrhetic acid, isoliquiritin, and liquiritin accumulation. Transcriptome profiling in this treatment identified 465 up-regulated and 1,109 down-regulated genes. GO annotation involved 1,108 differentially expressed genes, and KEGG analysis was primarily enriched in the plant-pathogen interaction pathway. Furthermore, transcription factor analysis revealed alterations in the C2H2, NAC, and MYB families, which are associated with phosphorus response.